SOSIALISASI DAN PENDAMPINGAN PENGGUNAAN ALAT PEMBUKA TIRAM RAMAH LINGKUNGAN PADA MASYARAKAT PESISIR KABUPATEN BARRU - Sintia Salam; Nabila Nasir; Melda Longde; Rifda Nur Hikmahwati Arif; Salma Samputri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service program was implemented to optimize the use of an environmentally friendly oyster opening tool named Ecosmart Oyster as a solution to issues of efficiency, work safety, and the low economic value of traditional oyster processing carried out by coastal communities in Lajari Village, Barru Regency. Currently, the oyster opening process still relies on manual knives that require great effort, considerable time, and pose a high risk of injury. Furthermore, traditional methods often damage oyster shells, thereby reducing the potential utilization of shell waste as economically valuable products. Through the Ecosmart Oyster innovation, this program aims to improve the effectiveness of the oyster opening process, minimize the risk of workplace accidents, and encourage the transformation of oyster waste into an additional source of income for the community. The program was carried out through several main stages: preliminary study to identify community needs, socialization of the tool to fishermen and oyster processing entrepreneurs, implementation and intensive assistance in tool usage, monitoring and evaluation of tool effectiveness, and dissemination of results to the village government and wider community. A participatory approach was employed throughout all activities to ensure active community involvement in the learning process and enable independent tool operation. Program results demonstrate that the use of Ecosmart Oyster can increase oyster opening efficiency by 45–50% compared to manual methods, with average opening time decreasing from 30 seconds to only 15 seconds per oyster. Additionally, no injuries were reported during the training and implementation process, indicating a high level of tool safety. The integrity of oyster shells was also better maintained, thereby opening opportunities for their utilization as craft materials, planting media, animal feed, or calcium fertilizer. Community enthusiasm, ease of tool use, and low maintenance costs further support the sustainability of this program. In conclusion, this community service program successfully enhanced the community's capacity to process oysters more productively, safely, and sustainably.